EFFICACY OF CHEMICAL WEED CONTROL IN MAIZE (Zea mays) (International Journal of Food and Nutritional Sciences, 2022)
A field experiment entitled “Efficacy of Chemical Herbicide for Weed Control in Maize” (Zea mays L.) was conducted on medium black soil at Instructional Farm, College of Agriculture, Loni during Kharif season of 2020-21 & 2021-22.To test the efficacy of herbicides at higher and lower rate against different species along with cultural methods treatments consists of Atrazine @ 700 & 1000 g a.i. ha., Pendimethalin (PE) @ 900 &@ 1200 g a.i. ha., Tembotrione (POE) 100 &120 g a.i. ha., 2HW and 2IC at 20 & 40 DAS and Unweeded control.Tembotrione ( POE )@ 120 and 100 g a.i. ha-1was quite effective in reducing the count of monocot , dicot and sedges during 2020-21 and 2021-22. The results of the experiment indicated that significantly higher yield attributes and yield of maize in 2 HW and 2IC at 20 and 40 DAS and was followed by tembotrione @ 120 & 100 g a.i. ha-1 , Atrazine @ 1000 & 750 g a.i. ha-1 , Pendimethalin @ 1200 & 900 g a.i. ha-1during 2020-21 & 2021-22 respectively.